Penicillium janthinellum NCIM1366 shows improved biomass hydrolysis and a larger number of CAZymes with higher induction levels over Trichoderma reesei RUT-C30 - Sreeja-Raju, Athiraraj; Christopher, Meera; Kooloth-Valappil, Prajeesh; Kuni-Parambil, Rajasree; Gokhale, Digambar Vittal; Sankar, Meena; Abraham, Amith; Pandey, Ashok; Sukumaran, Rajeev K. (Biotechnology for Biofuels, 2020)
Background Major cost of bioethanol is attributed to enzymes employed in biomass hydrolysis. Biomass hydrolyzing enzymes are predominantly produced from the hyper-cellulolytic mutant filamentous fungus Trichoderma reesei RUT-C30. Several decades of research have failed to provide an industrial grade organism other than T. reesei, capable of producing higher titers of an effective synergistic biomass hydrolyzing enzyme cocktail. Penicillium janthinellum NCIM1366 was reported as a cellulase hyper producer and a potential alternative to T. reesei, but a comparison of their hydrolytic performance was seldom attempted. Results Hydrolysis of acid or alkali-pretreated rice straw using cellulase enzyme preparations from P. janthinellum and T. reesei indicated 37 and 43% higher glucose release, respectively, with P. janthinellum enzymes. A comparison of these fungi with respect to their secreted enzymes indicated that the crude enzyme preparation from P. janthinellum showed 28% higher overall cellulase activity. It also had an exceptional tenfold higher beta-glucosidase activity compared to that of T. reesei, leading to a lower cellobiose accumulation and thus alleviating the feedback inhibition. P. janthinellum secreted more number of proteins to the extracellular medium whose total concentration was 1.8-fold higher than T. reesei. Secretome analyses of the two fungi revealed higher number of CAZymes and a higher relative abundance of cellulases upon cellulose induction in the fungus. Conclusions The results revealed the ability of P. janthinellum for efficient biomass degradation through hyper cellulase production, and it outperformed the established industrial cellulase producer T. reesei in the hydrolysis experiments. A higher level of induction, larger number of secreted CAZymes and a high relative proportion of BGL to cellulases indicate the possible reasons for its performance advantage in biomass hydrolysis.
Keywords: Bioethanol; CAZymes; Cellulase; Penicillium janthinellum; Secretome; Trichoderma reesei

Cellulase hyper-producing fungus penicillium janthinellum NCIM 1366 elaborates a wider array of proteins involved in transport and secretion, potentially enabling a diverse substrate range - Christopher, Meera; Sreeja-Raju, Athiraraj; Kooloth-Valappil, Prajeesh; Gokhale, Digambar Vitthal; Sukumaran, Rajeev K. (Bioenergy Research, 2023)
The efficient breakdown of lignocellulose requires the concerted activity of multiple enzymes. Previous studies on Penicillium janthinellum NCIM 1366 (PJ-1366) have revealed a more versatile repertoire of cellulases as compared to the hypercellulolytic strain Trichoderma reesei RUT-C30. Since a robust transport and secretion network is necessary to achieve proficient enzyme production, the transporters and extracellular proteins of PJ-1366 identified from its genome data were compared with those of Penicillium rolfsii (the phylogenetically closest species) and T. reesei RUT-C30 (the industrial work horse for cellulase production). Transmembrane proteins formed 20.4%, 21.0% and 18.2%, respectively of the proteome of PJ-1366, P. rolfsii and T. reesei RUT-C30, and 292 of them were mapped as transporters in PJ-1366. Major facilitator superfamily transporters (264) and sugar transporters (167) are abundant in PJ-1366, which probably aid in the uptake of oligosaccharide inducers of cellulase. The number of extracellular proteins (1007) in PJ-1366 is the highest reported for a Penicillium species. Also, PJ-1366 encoded 1.5 x more proteins involved in carbohydrate metabolism than the other fungi, and its secreted CAZymes belonged to much more diverse families (73), potentially enabling the fungus to act on heterogenous substrates. Structural differences in some untranslated protein response (UPR) effectors like Pdi and Clx detected in PJ-1366 may facilitate unique modes of cellulase regulation.
Keywords: Cellulase; Pathway; Penicillium; regulation; Secretion; Transport